1983
DOI: 10.1128/jvi.45.3.925-940.1983
|View full text |Cite
|
Sign up to set email alerts
|

Organization of chicken DNA sequences homologous to the transforming gene of avian myeloblastosis virus. II. Isolation and characterization of lambda proto-amv DNA recombinant clones from a library of leukemic chicken DNA

Abstract: Several lambda proto-amv recombinants isolated from a lambda Charon 4A library of leukemic chicken DNA were analyzed by using various restriction endonucleases and hybridization with specific probes representing different regions of the transforming gene of avian myeloblastosis virus. The position of 30 sites for 11 different restriction endonucleases was established in the proto-amv region of chicken DNA. Identical restriction endonuclease maps were obtained for the normal and leukemic DNAs in the proto-amv d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These data, together with the functional criterion that posthatch inoculation with this virus resulted in typical lymphoid leukosis (see below), allowed us to conclude that the virus used in these experiments was RAV-1. (31). Of 13 sites examined in this study, all were confirmed in SC strain chicken DNA by Southern analysis with v-myb-derived probes.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…These data, together with the functional criterion that posthatch inoculation with this virus resulted in typical lymphoid leukosis (see below), allowed us to conclude that the virus used in these experiments was RAV-1. (31). Of 13 sites examined in this study, all were confirmed in SC strain chicken DNA by Southern analysis with v-myb-derived probes.…”
Section: Resultsmentioning
confidence: 68%
“…Of 13 sites examined in this study, all were confirmed in SC strain chicken DNA by Southern analysis with v-myb-derived probes. Additional restriction sites were mapped in clone X121, provided by M. Baluda (31). v-myb-homologous exons are indicated by open boxes.…”
Section: Resultsmentioning
confidence: 99%
“…Of 13 sites examined in this study, all were confirmed in SC strain chicken DNA by Southern analysis with v-myb-derived probes. Additional restriction sites were mapped in clone 121 provided by M. Baluda (37). v-myb homologous exons are indicated by shaded boxes; c-myb exons 5' of v-myb homologous sequences are indicated by open boxes.…”
mentioning
confidence: 99%
“…Avian myeloblastosis virus (AMV) is a replication-defective retrovirus that transforms hematopoietic cells in vitro (3, 39) and induces myeloblastic leukemia in vivo (6,39,55). The tumorigenicity of AMV has been attributed to a nucleotide sequence, designated v-myb (16), which is located at the 3' end of the viral genome (18,31,49,58) and probably arose by the integration of several exons of a cellular gene known as c-myb (4, 20,30,[46][47][48]58). Expression of v-myb proceeds through a spliced subgenomic messenger RNA of 2.0 kilobases (kb) (14,22) which is translated into a 45,000to 48,000-Mr protein (13,32).…”
mentioning
confidence: 99%